Influence of triangular obstacles on droplet breakup dynamics in microfluidic systems - Azadeh Tazikeh Lemeski; Seyyed Masoud Seyyedi; Mehdi Hashemi-Tilehnoee; Azadeh Sadat Naeimi (Scientific Reports)
Abstract Microfluidic devices with complex geometries and obstacles have attracted considerable interest in biomedical engineering and chemical analysis. Understanding droplet breakup behavior within these systems is crucial for optimizing their design and performance. This study investigates the influence of triangular obstacles on droplet breakup processes in microchannels. Two distinct types of triangular obstructions, positioned at the bifurcation (case I) and aligned with the flow (case II), are analyzed to evaluate their impact on droplet behavior. The investigation considers various parameters, including the Capillary number (Ca), non-dimensional droplet length (L*), non-dimensional height (A*), and non-dimensional base length (B*) of the triangle. Utilizing numerical simulations with COMSOL software, the study reveals that the presence of triangular obstacles significantly alters droplet breakup dynamics. Importantly, the shape and location of the obstacle emerge as key factors governing breakup characteristics. Results indicate faster breakup of the initial droplet when the obstacle is positioned in the center of the microchannel for case I. For case II, the study aims to identify conditions under which droplets either break up into unequal-sized entities or remain intact, depending on various flow conditions. The findings identify five distinct regimes: no breakup, breakup without a tunnel, breakup with a tunnel, droplet fragmentation into unequal-sized parts, and sorting. These regimes depend on the presence or absence of triangular obstacles and the specific flow conditions. This investigation enhances our understanding of droplet behavior within intricate microfluidic systems and provides valuable insights for optimizing the design and functionality of droplet manipulation and separation devices. Notably, the results emphasize the significant role played by triangular obstacles in droplet breakup dynamics, with the obstacle’s shape and position being critical determinants of breakup characteristics.